Perlunya kewaspadaan pengelolaan risiko akibat rentannya pembiayaan pada bank syariah - Annisa, Maulidya (Maliki Interdisciplinary Journal, 2024)
Islamic banks, apart from generating most of their income from financing, are also the biggest source of business operational risk. This is due to the fact that problematic financing will reduce the profits and health of Islamic banks, which in turn will have a negative impact on their deposit customers. Because risk analysis, identification, measurement, supervision and control of financing risks must be carried out in a manner that is in accordance with sharia banking practices. The purpose of writing this article is to find out what financing is, financing risks and solutions to financing risks. The research in this article was carried out with using library research through theoretical studies and other related reference sources. Based on the article written by the author, the author found a solution to overcome awareness of financing risks.